Investing in sustainable business models makes good business sense to Incofin - Popova, Viktoria (Technical Centre for Agricultural and Rural Cooperation, 2019)
Viktoria Popova, Technical assistance Manager at INCOFIN Investment Management, explains how they help smallholder farmers diversifying their products and help them be resilient to climate change